Ham Sok Hon, a Pioneer of Korean Cosmopolitanism - Song-Chong Lee (Religions, 2020)
This paper discusses an aspect of Ham Sok Hon’s philosophy, which the author argues would reflect, and contribute to enriching, the theory of cosmopolitanism. Ham was arguably one of the 20th century’s most influential, yet controversial, thinkers and political activists—particularly in the progressive movement of modern Korea. The author revisits his philosophy of ssial/saengmyŏng to find a more persuasive metaphysical ground to draw an enlarged and deepened sense of community than that of dominant cosmopolitan theories. To properly place his philosophy within the larger discussion of cosmopolitanism and highlight its uniqueness, the author presents a brief overview of major cosmopolitan theories first, along with their shortcomings, and then constructs Ham’s cosmopolitan vision by focusing on three specific insights: (1) ssial/saengmyŏng (씨알/生命, life) as the agent, (2) religion and politics for ipch’ejŏk in’gan (立體的人間 the multi-dimensional human), and (3) narrative and memory as the driving force of cosmopolitanism.